Involvement of Mice Hippocampus Brain-derived Neurotrophic Factor in Diazinon-induced Depressive Behavior in Mice - Mehdi Aliomrani (Iranian Journal of Toxicology, 2022)
Background: Diazinon (Dzn), an Organophosphorus (OP) pesticide, is extensively used in agriculture. Acetylcholinesterase inhibition is linked to OP toxicity, and there are major mental health concerns associated with the use of pesticides. The objective of this study was to assess the depressive behavior in an animal model following their exposure to Dzn and the effect on the Brain-Derived Neurotrophic Factor (BDNF) as a critical neurotropic factor. Methods: Male Swiss mice (N=42; 25±3g each) were used and their behaviors were eamined on including the locomotor, Forced Swimming (FST), and Sucrose Preference (SP) tests. These tests were performed the day after a single daily Dzn administration by gavage (2.5-20 mg/kg). Specific animal groups were exposed to Dzn daily (2.5-10 mg/kg) for 14 days, and a test was performed on days 7 and 15. Results: Following the acute exposure to Dzn, the animals’ locomotor activity did not change significantly. During the FST, Dzn at 20 mg/kg significantly increased the animals’ immobility time, indicating despair behavior. Imipramine, injected intraperitoneally at 10 mg/kg, did not cause the depressive behavior. The subacute exposure to Dzn induced less locomotor activity than that of the controls. The 7-day exposure to Dzn at 10 mg/kg significantly prolonged the immobility period compared to that of the controls. The 14-day Dzn exposure at 2.5, 5, or 10 mg/kg increased the immobility time significantly compared to that of the controls. None of the treatment groups showed SP, clearly showing animal anhedonia. The BDNF levels significantly decreased not only by subacute exposures to Dzn but also following a single exposure to this this pesticide. Conclusion: The acute and subacute exposure to Dzn induced depressive behavior and increased the BDNF levels in the hippocampus of Swiss male mice following exposure to Dzn at varying doses of 2.5, 5, or 10 mg/kg.